The experiences of patients and their family members when receiving bad news about cancer: A qualitative meta‐synthesis. Issue 12 (30th October 2019) - Matthews, Tamyra; Baken, Donald; Ross, Kirsty; Ogilvie, Emily; Kent, Lizzy
Abstract: Objective: This qualitative meta‐synthesis explored the subjective experiences of patients and their family members when receiving bad news about cancer, with a focus on what was important to them during this process and making future recommendations. Methods: A search of five electronic databases yielded 587 different records that resulted in 88 articles assessed against the inclusion/exclusion criteria. With the supplement of four additional records, 29 articles were analysed using thematic synthesis. A quality appraisal checklist was used to provide further information about the included articles. Results: Patients and family members experienced receiving bad news as a process that involved three phases, labelled as follows: "preparation", "delivery", and "adjusting and coping". The "preparation" phase had four themes: the setting, developing a relationship, knowing the patient, and forewarning. Four themes were identified during the "delivery" phase: emotional reactions, empathy not sympathy, active participation, and understanding. "Adjusting and coping" comprised four themes: hope, holistic support, being a protector, and ongoing relationships. Conclusions: Receiving bad news is a significant experience for patients and family members. They want bad news delivered in an appropriate setting, in a manner consistent with their personal preferences, and have their psychological needs attended to within the context of an established relationship. Healthcare professionals can be assisted to deliver bad news in the best way possible by additional training and their workplace institutions providing quiet, private rooms, and sufficient time. Future research is needed to better understand family members' experiences and needs.